Gambaran Jumlah Hitung Jenis Leukosit pada Penderita Hepatitis B di Salah Satu Rumah Sakit Yogyakarta - Citra Agung Hiola; Shafriani, Nazula Rahma; Bimantara , Arif (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Hepatitis B is a serious infectious disease that can cause progressive liver damage and affect the body's immune system. This study aims to describe the profile of leukocyte counts and types in Hepatitis B patients as an indicator of the body's immune response. The study was conducted as an observational study using a descriptive quantitative approach and a cross-sectional design on 70 medical records of patients at a hospital in Yogyakarta from January to December 2024. The analysis results showed that the most commonly increased leukocyte types were neutrophils (47.1%) and monocytes (10%), while lymphocytes (50%) and eosinophils (34.3%) were most frequently decreased. Basophils were mostly within normal limits (98.6%). These findings indicate the activation of the innate immune system through neutrophilia, as well as a decrease in the adaptive immune system due to lymphocytopenia. These results highlight the importance of hematological examinations as an additional parameter in assessing the infection phase and immune response of Hepatitis B patients. Leukocyte examinations can also serve as a basis for clinical decision-making, particularly in monitoring therapy and disease progression.